2023
DOI: 10.3390/foods12071353
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches for Improving the Quality of Processed Fruits and Vegetables and Their By-Products

Abstract: The 2030 Sustainable Development Agenda calls for all social actors to contribute to significant societal and environmental issues [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…It is widely recognized that fruits and vegetables play an essential role in maintaining a healthy diet. Fruits and vegetables serve as vital sources of nutrients an provide extensive health benefits [4,7,14,16,[26][27][28]. Insufficient intake of fruits and vegetables is estimated to contribute to 14% of worldwide gastrointestinal cancer deaths, 11% of deaths attributable to ischemic heart disease, and 9% of deaths caused by stroke [29].…”
Section: Minimally Processed Fruits and Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that fruits and vegetables play an essential role in maintaining a healthy diet. Fruits and vegetables serve as vital sources of nutrients an provide extensive health benefits [4,7,14,16,[26][27][28]. Insufficient intake of fruits and vegetables is estimated to contribute to 14% of worldwide gastrointestinal cancer deaths, 11% of deaths attributable to ischemic heart disease, and 9% of deaths caused by stroke [29].…”
Section: Minimally Processed Fruits and Vegetablesmentioning
confidence: 99%
“…Contamination of vegetables can occur at various stages: in the pre-harvest phase while the plant is in the field, during harvesting, and in the post-harvest phase, encompassing transport, processing, or packaging [28,45,46,51,57]. The different stages of salad processing involve several steps, as observed in Figure 1: Typically, initial contamination in the plant reflects its environmental microbiota [51,56].…”
Section: Main Sources Of Microbiological Contamination Throughout The...mentioning
confidence: 99%
“…Preparing the raw material before pretreatment is intended to minimize unfavorable changes occurring during the actual processes. Moreover, by manipulating the process parameters themselves, it is possible to increase the efficiency of the process and obtain a product attractive to a potential consumer [7][8][9]. In addition, pretreatment reduces the level of hazardous chemicals accumulated in raw materials, resulting from excessive soil fertilization and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In investigations of foodborne outbreaks caused via vegetables and fruits, the focus is usually only on the final stage of the vegetable and fruit production chain (Santos et al, 2023). However, it is important to recognize that contamination of fresh fruits and vegetables can occur at various stages, including the pre-harvest phase in the field, during harvesting, and in the post-harvest phase involving transportation, processing, or packaging (Balali et al, 2020;Miller et al, 2023;Santos et al, 2023). Researches have indicated that factors such as the potential of hydrogen, water activity, nutrients, oxidation-reduction potential, irrigation water, climatic conditions, processing treatments, and transportation processes can all influence the level of Salmonella contamination in fresh fruits and vegetables (Thomas et al, 2024;Wadamori et al, 2017).…”
Section: Introductionmentioning
confidence: 99%